Effect of hunger and potential rewards on corruption - Yew, Joey May June (2018)
Past studies have consistently revealed that the lack of financial or physiological resources leads to an increase in resource-seeking behavior. For instance, low subjective socioeconomic status (SSES) is adequate to stimulate increased liking and consumption and for high-caloric and high-energy foods. In addition, it has been found that physiological deprivation (i.e., hunger) drives individuals to engage in domain-specific unethical behavior (i.e., cheating for food). However, it is unknown whether physiological deprivation (i.e., hunger) would lead to non-need-related resource seeking behavior (i.e., corruption), and how SSES may moderate this relationship. Hence, the present study examined how hunger affected corruptive tendency in individuals. Ninety-three Singapore undergraduates were randomly allocated to either the fasted or control condition, in which participants in the fasted condition were instructed to fast the night before the experiment. Five captions were presented to all participants and a caption was accompanied with a hypothetical bribe to capture their corruptive tendency in terms of their likelihood to accept the bribe. Individuals’ SSES were also measured using the adapted MacArthur’s SES scale. There were no significant differences between fasted and control condition in the likelihood to accept bribe, and neither did SSES moderated such relationship. Limitations, future directions, theoretical and practical implications of this study were discussed.